Interactive caseware for teaching - Desberg, Peter; Trimble, Kimberly; Colbert, Joel. (Boston : Allyn and Bacon, 1995)
Users of this software analyze seven'real-life' classroom management situations by identifying areas where teachers are having difficulties and reviewing commentary on theoretical positions.
CD is corrupted and obsoluted.
System requirements: Macintosh; CD-ROM drive; 5 MB of RAM; HyperCard 2.x or higher or HyperCard Player.
Keywords: Classroom management -- Software; Teaching -- Case studies -- Software